Critical ethnography method, ethics, and performance - Madison, D. Soyini (SAGE, 2012)
"This text presents a fresh new look at critical ethnography by emphasizing the significance of ethics and performance in the art and politics of fieldwork. The book explores an ethics of ethnography while illustrating the relevance of performance ethnography across disciplinary boundaries. The new edition is comprehensive, incorporating more extended discussions on theories and methods, thereby providing the reader with a broad range of considerations and choices. It also includes chapters on visual culture and performance"--Provided by publisher.